Enhanced adherence counselling completion rates, viral load suppression in people with HIV in Africa: systematic review and meta-analysis - Hafidha M. Bakari; Oluwafemi Alo; Mariam S. Mbwana; Swalehe M. Salim; Zuhura M. Ally; Rahma Musoke; Emilie Ludeman; Taylor Lascko; Natalia Blanco; Habib O. Ramadhani (Discover Public Health)
Abstract Background The World Health Organization recommended enhanced adherence counselling (EAC) sessions among people with HIV on ART with persistent viremia (viral load > 1000 copies/ml). There have been variations on the impact of EAC on viral load suppression (VLS) and it is unclear whether completing three sessions as recommended by country’s HIV treatment guidelines is superior to those who had less than three sessions. We summarized pooled estimates of EAC linkage, completion rate, VLS and compared impact of EAC linkage, EAC completion on VLS among people with HIV in Africa. Methods Through systematic review, PubMed, Embase, Cochrane CENTRAL and clinicaltrials.gov were searched for articles published between January 2016 and December 2022. Participants who attended three EAC sessions were considered to have completed and VLS was defined as HIV-RNA < 1000 copies/ml. Using random effects models, we computed pooled prevalence estimates with a 95% confidence interval (CI). Comparison was quantified by absolute risk difference (RD). Results A total of 12-studies were included in the final analysis. Overall, the pooled EAC linkage was 85.1%, EAC completion was 63.8%, VLS was 51.2% and regimen switch was 51.8%. Linkage to EAC was associated with increased likelihood of achieving VLS compared to not linking to EAC(RD = 0.09; 95%CI 0.00–0.18; p = 0.05). Compared to those who did not complete EAC sessions, those who completed were more likely to be virally suppressed, although results were not statistically significant, (RD = 0.07; 95%CI -0.08–0.23; p = 0.36). Conclusions Among people living with HIV eligible for EAC services, nearly 15% were not linked and 36% did not complete three EAC sessions. In addition to EAC, other interventions are needed to support persons with persistent viremia in the efforts of achieving HIV epidemic control.